2020
DOI: 10.1016/j.peptides.2019.170207
|View full text |Cite
|
Sign up to set email alerts
|

GIP analogues augment bone strength by modulating bone composition in diet-induced obesity in mice

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…However, overall effects of GIP at pharmacological concentrations are likely to be protective against atherosclerosis both in non-diabetic and diabetic conditions in vivo. Furthermore, recent in vivo studies have demonstrated multiple beneficial effects of GIP on diabetes-related diseases, such as Alzheimer's disease [129][130][131][132][133][134] and osteoporosis [135][136][137][138][139][140][141][142][143][144][145][146]. These findings suggest that dual or triple agonists including GIPR, which will be available in the near future [54][55][56], could be comprehensive treatment for diabetes and its related disorders.…”
Section: Discussionmentioning
confidence: 95%
“…However, overall effects of GIP at pharmacological concentrations are likely to be protective against atherosclerosis both in non-diabetic and diabetic conditions in vivo. Furthermore, recent in vivo studies have demonstrated multiple beneficial effects of GIP on diabetes-related diseases, such as Alzheimer's disease [129][130][131][132][133][134] and osteoporosis [135][136][137][138][139][140][141][142][143][144][145][146]. These findings suggest that dual or triple agonists including GIPR, which will be available in the near future [54][55][56], could be comprehensive treatment for diabetes and its related disorders.…”
Section: Discussionmentioning
confidence: 95%
“…GLP‐1 receptor mediated improvements in bone strength and quality have also been demonstrated in various distinct forms of diabetes including insulin‐deficient type 1 diabetic mice (Mansur et al, 2015), insulin‐resistant high fat fed diabetic mice (Mansur et al, 2019a) as well as genetically induced type 2 diabetic animal models (Sun, Lu, et al, 2016). The observed positive actions of sitagliptin on bone are likely due to the elevations of both GLP‐1 and GIP levels (Mansur et al, 2019b), given that GIP has well documented benefits on bone in animals and humans (Gobron et al, 2020; Mabilleau et al, 2016; Mabilleau, Gobron, et al, 2018; Stensen et al, 2020; Vyavahare et al, 2020). In the clinic, recent reports show exenatide to have no impact on bone fractures, whereas lixisenatide and liraglutide reduce fracture occurrence (Cheng et al, 2019).…”
Section: Glp‐1 and The Endocrine Pancreasmentioning
confidence: 99%
“…However, only Ac3IV significantly reduced circulating LDL-cholesterol and triglyceride levels, highlighting this as a distinct advantage over exendin-4, given that diabetes and obesity represent key risk factors for cardiovascular disease. 46 In addition, obesity-driven forms of diabetes are also associated with increased occurrence of bone fragility fractures, 47,48 and both Ac3IV and exendin-4 augment bone mineral content and density, implying another potentially important therapeutic benefit. Despite this, it should also be noted that increased levels of copeptin, a peptide co-secreted with AVP and considered as an excellent surrogate marker for assessing circulating AVP concentrations, 49 is associated with metabolic dysregulation and onset of diabetes.…”
Section: Both Peptide Interventions Decreased Circulating Glucose Bodymentioning
confidence: 99%